FAKTOR-FAKTOR YANG BERKORELASI DENGAN KEPATUHAN PEMILIK DEPOT AIR MINUM ISI ULANG DALAM PEMERIKSAAN BAKTERIOLOGIS - Rosalina Helen Purwitasari; Zulkarnaini Zulkarnaini; Suyanto Suyanto (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
The high of public interested in refill drinking water depots it caused the existence of more refill drinking water depots, but not all of the drinking water depots that guaranteed product was safety, one of the uses was the absence of routine bacteriological examination by the depot owner like the Minister of Health Regulation mandated No. 736 / Menkes / Per / IV / 2010. In 2015, The Kuantan Singingi District had 260 depots, but more than 50% depots did not carry out routine with bacteriological checks. The purpose of this research was to analyze the factors that correlated to the compliance of refill drinking water depot owner in bacteriological examination. This research was conducted in November 2017 until January 2017 that located in Kuantan Singingi Regency. The research method that used was survey. The population in this research was the all of drinking water depot in Kuantan Singingi regency as much 260 depots with the sample total number 72 depots with proportionate stratified random sampling technique. The instruments of data collection taht used were questionnaires and observation sheets. The data analysis was done by spearman rho analysis. Based on the result of this research, it was known that the examination cost, the supervision of health personnel and physical environment with compliance of bacteriological examination correlated with medium and positive correlation coefficient value of each 0.527; 0.410; 0.441 and p value of each 0.000. It was expected that the local of governments could provide the health laboratories and health offices to increase the regular surveillance of refill drinking water owners.